Multivariate risk-neutral pricing of reverse mortgages under the Bayesian framework - Jackie Li; Atsuyuki Kogure; Jia Liu (Risks, 2019)
In this paper, we suggest a Bayesian multivariate approach for pricing a reverse mortgage, allowing for house price risk, interest rate risk and longevity risk. We adopt the principle of maximum entropy in risk-neutralisation of these three risk components simultaneously. Our numerical results based on Australian data suggest that a reverse mortgage would be financially sustainable under the current financial environment and the model settings and assumptions.
Keywords: 330; reverse mortgage; house price risk; interest rate risk; longevity risk; risk-neutralisation; principle of maximum entropy; Bayesian modelling